AKTIVITAS INHIBITOR TIROSINASERUMPUT LAUT Halimeda Spp DARI PESISIR ACEH BARAT - Mohamad Gazali (Universitas Teuku Umar, 2018)
Seaweeds have been utilized by local community as foodstuff, cosmeceutical, traditional drug and others. There are three major groups of seaweeds namely brown algae (Phaeophyta), red (Rhodophyta) and green (Chlorophyta). Halimeda sppis one of green algae which sufficiently dominant at the coastal of WestAceh. Seaweed contains bioactive compound which can serve as a defense from ultraviolet radiation that caused hyperpigmentation effect. The purpose of this study is to analyse the tyrosinase inhibitory activity of Halimeda sppextract from WestAceh. The results shown that the methanol extract of Halimeda spppossess phytochemical properties such as ekstrak Halimeda spp mengandung senyawa alkaloid, flavonoid, phenol, tannin and steroid. Tyrosinase inhibitory activity of Halimeda sppmethanol extract is the best extract which can be inhibit monophenolase with IC50 : 57300,660µg/ml and IC50 = 3981685,489µg/ml in diphenolase pathway with kojic acid as positive control. Moreover,etyl acetateand n-hexane extract have no activity of tyrosinaseinhibitor. Therefore, new finding of tyrosinase inhibitor agent from green algae Halimeda sppgive the fruitfull information forcosmeceutical industry. Halimeda sppparts could be complementaryeach other in providing the raw material of cosmetic product.